1997
DOI: 10.1006/jema.1996.0105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information on Land Development: a Dynamic and Stochastic Analysis

Abstract: In a two period model of land development, Arrow and Fisher, and Henry have shown that when development is both indivisible and irreversible, a developer who ignores the possibility of obtaining new information about the outcome of such development will invariably underestimate the benefits of preservation and hence favor development. This paper extends aspects of this literature by (i) studying the development question in a dynamic and stochastic framework, and (ii) explicitly incorporating an information pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 9 publications
(14 reference statements)
0
35
0
Order By: Relevance
“…An examination of the social planner's optimization problem when partial stopping is a 20Por more on this literature, see Pindyck (1991), Dixit and Pindyck (1994), and Batabyal (1996Batabyal ( , 1997. The present paper differs from Batabyal (1996) in three ways.…”
Section: Discussionmentioning
confidence: 87%
“…An examination of the social planner's optimization problem when partial stopping is a 20Por more on this literature, see Pindyck (1991), Dixit and Pindyck (1994), and Batabyal (1996Batabyal ( , 1997. The present paper differs from Batabyal (1996) in three ways.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, Titman (1985), Capozza and Helsley (1990), and Batabyal (1996Batabyal ( , 1997Batabyal ( , 2000 have studied the subject of land development under uncertainty. In Titman's (1985) model, he first assumes that the value of vacant land in the first period exceeds the wealth of a landowner who wishes to construct a building.…”
mentioning
confidence: 99%
“…Analogously, in the continuous-time analysis of Batabyal (1997) , the infinitesimal look ahead stopping rule (ILASR) is utilized to determine when a stochastic "revenue from development" process should be terminated. The paper that is closest to our paper is Batabyal (2000).…”
mentioning
confidence: 99%
“…Recently, this kind of analysis has been extended by Batabyal (1995Batabyal ( , 1996a, Capozza and Helsley (1990), and Clarke and Reed (1990) to study the development question in a multiperiod framework. However, very little is known about the nature of the development decision when this decision is divisible.…”
mentioning
confidence: 99%
“…As such, one can ask whether the APH result holds in more general settings in which the development decision (i) is being made in a multiperiod setting, and (ii) is divisible. With regard to the multiperiod nature of the development decision, Batabyal (1995Batabyal ( , 1996a, Capozza and Helsley (1990), and Clarke and Reed (1990) have already shown that the prodevelopment bias described by APH does carry over, but in a somewhat modified form.…”
mentioning
confidence: 99%